Groundwater Retention Based on Toposequence in People’s Oil Palm Plantations - Utami, Wanda Afrilia; Hermawan, Bandi; Prawito, Priyono; Barchia, Muhammad Faiz; Sukisno; Putri, Elsa Lolita (TERRA : Journal of Land Restoration, 2024)
Soil, water, and crops are interdependent components of agricultural systems, and understanding their characteristics and interactions is critical for effective agricultural management. This study investigates the relationship between soil water-holding capacity and varying land slope gradients. The research was conducted on a community oil palm plantation in Talang Tengah I Village, Pondok Kubang District, Central Bengkulu Regency. A purposive sampling method was applied at five slope categories: flat (0–8%), sloping (8–15%), moderately steep (15–25%), steep (25–45%), and very steep (45–100%). Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 7.0 software. The findings demonstrate a significant influence of slope on soil water-holding capacity. Increasing slope gradients are associated with reduced soil permeability, increased bulk density, decreased total pore space, and lower soil organic carbon content, collectively leading to diminished water-holding capacity. The developed model accurately represents the relationships between variables, indicating that slope directly affects organic matter, sand content, and permeability, while bulk density impacts total pore space and permeability, which in turn influence water-holding capacity. The results emphasize the importance of considering land slope in soil and water management strategies to optimize agricultural productivity. Future applications of this model could guide sustainable land-use planning and inform erosion control measures to maintain soil quality and water availability in sloped agricultural landscapes